Divided attention at encoding or retrieval interferes with emotionally enhanced memory for words. Issue 3 (16th March 2021) - Yeung, Ryan C.; Fernandes, Myra A.
ABSTRACT: Emotional information is typically better remembered than neutral information. We asked whether emotional, compared to neutral, words were less vulnerable to the detrimental effects of divided attention. In two experiments, undergraduate students intentionally encoded words of intermixed valence (neutral, negative, or positive) and arousal (neutral, high, or low). Following a filled delay, memory was assessed with a free recall test. In Experiment 1, participants encoded visually-presented words under either full attention (FA; no distracting task) or divided attention (DA; concurrently making animacy decisions to auditorily-presented distractor words) in a counterbalanced, within-subjects design. As expected following FA at encoding, recall was significantly enhanced for negative compared to neutral words. Following DA at encoding, recall was significantly impaired across all valences. Critically, DA at encoding also eliminated the memory benefit for negative information: recall of negative words was no longer significantly different from neutral or positive words. In Experiment 2, we manipulated attention at retrieval rather than encoding. Remarkably, results from Experiment 1 were replicated: DA eliminated the well-known emotionality boost for negative words. In both experiments, memory for positive words did not significantly differ from neutral. Findings suggest that DA during either encoding or retrieval can interfere with the specific mechanisms by which negative emotion typically improves memory.